National Eye Service (1929)
1929 1929 1920s 12 pages [7] NATIONAL EYE SERVICE Under the new service these specialists can now be consulted by those of the general public who are either State-insured persons or the dependants of insured persons, and by all non-insured persons (including H.S.A. Contributors and their dependants) who cannot afford to pay the ordinary fee of an ophthalmic surgeon, and whose total family income does not exceed £250 per annum. The Advantage of the Service to those who use it The advantage of this complete ophthalmic medical service as against the purely optical testing carried out by opticians, is that a thorough examination is made with medical knowledge of cause and effect. The service provides for the protection of any and every phase of eye-trouble and ensures proper advice and treatment to preserve and safeguard the sight and the general health. Many people are now provided with spectacles which they do not actually need, but if an ophthalmic medical practitioner prescribes glasses, it is because they are necessary. Dispensing and fitting of glasses A fundamental feature of the service is that the dispensing of optical prescriptions is carried out by expert dispensing opticians who specialise in the measuring and fitting of the frame and lenses. In every case the work must be carried out to the satisfaction of the doctor prescribing 292/841.4/1/61